2015
DOI: 10.2337/db14-1847
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Intestinal Microbiota Correlate With Susceptibility to Type 1 Diabetes

Abstract: We tested the hypothesis that alterations in the intestinal microbiota are linked with the progression of type 1 diabetes (T1D). Herein, we present results from a study performed in subjects with islet autoimmunity living in the U.S. High-throughput sequencing of bacterial 16S rRNA genes and adjustment for sex, age, autoantibody presence, and HLA indicated that the gut microbiomes of seropositive subjects differed from those of autoantibody-free first-degree relatives (FDRs) in the abundance of four taxa. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
181
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(205 citation statements)
references
References 56 publications
9
181
1
7
Order By: Relevance
“…In the BABYDIET cohort study in Germany, subjects with a high abundance of Bacteroides at 6 months of age were at an increased risk of early autoantibody development, but this trend was not particularly prevalent in subjects included in the study [24]. Similar differences were not seen in a longitudinal case-control comparison in DIABIMMUNE, a study of Finnish and Estonian children [25], or in a cross-sectional study conducted in Denver, Colorado [26], possibly due to differences in study protocol, sample size, and geographic location (Table 1). Specifically, Finnish children enrolled in the DIABIMMUNE study were from Espoo, Finland whereas those with increased B. dorei enrolled in DIPP were from Turku, Finland.…”
Section: Bacteroidetesmentioning
confidence: 58%
See 2 more Smart Citations
“…In the BABYDIET cohort study in Germany, subjects with a high abundance of Bacteroides at 6 months of age were at an increased risk of early autoantibody development, but this trend was not particularly prevalent in subjects included in the study [24]. Similar differences were not seen in a longitudinal case-control comparison in DIABIMMUNE, a study of Finnish and Estonian children [25], or in a cross-sectional study conducted in Denver, Colorado [26], possibly due to differences in study protocol, sample size, and geographic location (Table 1). Specifically, Finnish children enrolled in the DIABIMMUNE study were from Espoo, Finland whereas those with increased B. dorei enrolled in DIPP were from Turku, Finland.…”
Section: Bacteroidetesmentioning
confidence: 58%
“…The microbial diversity of pre-autoimmune children is not well defined, with some studies reporting clear decreases in diversity prior to seroconversion [22,23] while other studies see no difference in diversity measures between those that seroconvert and healthy controls [25,26,30]. Meanwhile, a decrease in microbial diversity after seroconversion but prior to T1D onset was reported [25].…”
Section: Diversitymentioning
confidence: 95%
See 1 more Smart Citation
“…Негативні емоції на больовий синдром особливо небезпечні за на-явності супутніх захворювань, зокрема ЦД 1-го типу [15]. При цьому порушуються практично всі види обмі-ну речовин, характерним є ураження більшості органів і систем організму, що в подальшому призводить до ви-никнення тяжких ускладнень і високої летальності хво-рих [12][13][14]. Порушення регенераторної функції тка-нин, послаблення фагоцитарної активності макрофагів і лейкоцитів та зниження захисного бар'єру слизових оболонок сприяють посиленню адгезії мікроорганізмів та формуванню хронічних вогнищ інфекції, зокрема в піднебінних мигдаликах і приносових пазухах [11].…”
Section: вступunclassified
“…Some studies have found an association between antibiotic use during infancy or early childhood and the development of inflammatory bowel disease (IBD), suggesting that environmental factors, altering microbiota – especially in early childhood - may trigger inflammation(14, 15). Shifting the microbiota composition may induce autoimmune reactivity(16, 17). …”
mentioning
confidence: 99%